Finite Element Analysis of Schwarz P Surface Pore Geometries for Tissue-Engineered Scaffolds. (30th April 2012) - Shin, Jaemin; Kim, Sungki; Jeong, Darae; Lee, Hyun Geun; Lee, Dongsun; Lim, Joong Yeon; Kim, Junseok
Abstract : Tissue engineering scaffolds provide temporary mechanical support for tissue regeneration. To regenerate tissues more efficiently, an ideal structure of scaffolds should have appropriate porosity and pore structure. In this paper, we generate the Schwarz primitive (P) surface with various volume fractions using a phase-field model. The phase-field model enables us to design various surface-to-volume ratio structures with high porosity and mechanical properties. Comparing the Schwarz P surface's von Mises stress with that of triply periodic cylinders and cubes, we draw conclusions about the mechanical properties of the Schwarz P surface.